Structural model of enablers for Green Lean Six Sigma implementation in Malaysian manufacturing industries - Letchumanan, L. Thiruvarasu (2022)
Green Lean Six Sigma (GLSS) has been recently clarified as a business strategy contributing to improving the environmental sustainability performance of operations through adopting the 3R concept, i.e., reduce, reuse, and recycle. Despite its broadly acknowledged benefits and capabilities, practitioners in the manufacturing industry continue to remain cautious of its application due to having insufficient knowledge and culture. This indicates that there is a necessity for recognizing key factors enabling its implementation. In the Malaysian manufacturing context, the enabling factors have yet to be identified and evaluated. Thus, this study aimed to identify and analyse key enablers facilitating the GLSS implementation in the Malaysian manufacturing sector and to develop a structural model for the identified enablers towards the implementation of GLSS. The implemented methodological approach included two steps. Firstly, it performed a systematic review of leading studies on the topic which are rather scarce in the current context. The second step entailed the Factor Analysis (FA) method and the application of Interpretive Structural Modelling (ISM) mixed with Matriced‘ Impacts Croises-Multiplication Applique‘ and Classment (MICMAC), for analysing and finalizing the findings. The findings from the literature review revealed that publication growth has been rapid in the last ten years. It is expected to continue to rise due to its intellectual contribution to the environmentally-sustainable (green) manufacturing paradigm, which is regarded as an application of the emerging concept of circular economy. It is also discovered that India, the United Kingdom, and the United States have a massive number of publications and strong international collaborations, respectively. The empirical results obtained by the multiple methods indicated an interpretive structural model with five factors including Strategic Integrity, Human Resource Management, Eco-production, Eco-network, and Technologies and Tools. It was exposed as a result that there is a high correlation between Strategic Integrity and Human Resource Management, both possessing significant driving power. Strategic Integrity was found to be a major factor in the internal consistency of the GLSS factorial structure. Implications wise, this thesis detailed a contemporary study in the field and delivers valuable insights both theoretically and practically.